Optimal Design of Elastic Circular Plane Arches - Trentadue, Francesco; Fiore, Alessandra; Greco, Rita; Marano, Giuseppe C.; Lagaros, Nikos D. (Frontiers in Built Environment, 2020)
Even if arches represent an old structural system adopted in construction practice since two thousand years ago, they are still adopted just if large spans have to be covered. The structural efficiency of arches principally depends on optimal material exploitation, due to the minimization of the thrust curve eccentricity, which reduces structural material volume and weight. Although the millenarian use and a very abundant literature dealing with arches, there is still scope for design optimization, so this study is framed within this context, investigating plane circular arches under uniformly distributed vertical load and self-weight. The arches are simply supported with bending springs at end sections. In a first step an analytical solution of the arch static is derived in dimensionless form. Next, the volume of the arch is minimized. Finally the results are charted to allow their use in a design process.